2010
DOI: 10.1111/j.1399-0012.2010.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in the morbidly obese: complicated but still better than dialysis

Abstract: Obese patients are denied renal transplantation in many centers. We report results regarding obesity from a new transplant program (1999 through 2007). Six hundred and forty-two patients were transplanted: 439 patients with BMI < 30 (Group 1), 109 patients with BMI 30.1-34.9 (Group 2), and 89 patients with BMI > 35 (Group 3). Follow-up was at least one yr. Medical and surgical management was performed by the same team throughout the study period. There were no demographic differences between groups except for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 18 publications
2
32
0
1
Order By: Relevance
“…At least two recent studies have attempted to address this question. 8,9 Glanton et al . assembled a cohort of 7,521 patients who started dialysis between 1995 and 1999 and were eventually placed on a kidney transplant waiting list.…”
Section: Is Transplantation Beneficial Among Obese Patients With Esrd?mentioning
confidence: 99%
“…At least two recent studies have attempted to address this question. 8,9 Glanton et al . assembled a cohort of 7,521 patients who started dialysis between 1995 and 1999 and were eventually placed on a kidney transplant waiting list.…”
Section: Is Transplantation Beneficial Among Obese Patients With Esrd?mentioning
confidence: 99%
“…Several relatively small studies have demonstrated no significant adverse effect of recipient obesity on patient and graft survival. [9][10][11] On the other hand, larger studies of registry data have demonstrated significantly worse survival outcomes for obese recipients, including a study of more than 50,000 recipients in the US Renal Data System performed by Meier-Kreische 12 and a study of more than 27,000 recipients in the United Network for Organ Sharing database performed by Gore and colleagues. 13 Both of these studies, however, examined patients undergoing transplantation before 2000, so the results may be different in the modern era of more powerful immunosuppression and improved overall patient management.…”
mentioning
confidence: 96%
“…Previous studies have found RT to have a significantly lesser mortality rate compared with lifelong hemodialysis among this population. 15 Therefore, despite greater resource utilization, RT should not be withheld based on BMI. With respect to poorer fiscal outcomes, two adjustments may be made to improve current policy.…”
Section: Discussionmentioning
confidence: 99%
“…Both concluded that while RT had greater complication rates, transplantation was more favorable than lifelong dialysis. 15,16 …”
mentioning
confidence: 99%